1993
DOI: 10.2337/diacare.16.12.1565
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Blood Pressure, Glucose, and Lipid Levels of High-Monounsaturated Fat Diet Compared With a High-Carbohydrate Diet in NIDDM Subjects

Abstract: A diet rich in monounsaturated fat has beneficial effects on blood pressure and glucose metabolism, whereas no adverse effects on lipid composition in NIDDM subjects is detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
3
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 11 publications
9
81
3
1
Order By: Relevance
“…The cornerstone in the treatment of Type-2 DM is dietary intervention, and in several years the prescribed diet has been rich in carbohydrate whereas interest in metabolic effects of different fatty acids has come later. However, several studies have displayed bene®cial metabolic effects of dietary monounsaturated fatty acids (MUFA) in Type-2 DM (Garg et al, 1988;Bonanome et al, 1991;Garg et al, 1992aGarg et al, , 1992bRasmussen et al, 1993;Thomsen et al, 1995a;Lerman-Garber et al, 1994a, 1994bNielsen et al, 1995). Interestingly, we recently showed bene®cial effects of MUFA diets on the diurnal blood pressure and von Willebrand Factor (vWF) in normotensive Type-2 DM subjects without proteinuria, both compared with a diet rich in carbohydrate (Rasmussen et al, 1994) and a diet rich in polyunsaturated fatty acids (Thomsen et al, 1995a(Thomsen et al, , 1995b.…”
Section: Introductionmentioning
confidence: 76%
“…The cornerstone in the treatment of Type-2 DM is dietary intervention, and in several years the prescribed diet has been rich in carbohydrate whereas interest in metabolic effects of different fatty acids has come later. However, several studies have displayed bene®cial metabolic effects of dietary monounsaturated fatty acids (MUFA) in Type-2 DM (Garg et al, 1988;Bonanome et al, 1991;Garg et al, 1992aGarg et al, , 1992bRasmussen et al, 1993;Thomsen et al, 1995a;Lerman-Garber et al, 1994a, 1994bNielsen et al, 1995). Interestingly, we recently showed bene®cial effects of MUFA diets on the diurnal blood pressure and von Willebrand Factor (vWF) in normotensive Type-2 DM subjects without proteinuria, both compared with a diet rich in carbohydrate (Rasmussen et al, 1994) and a diet rich in polyunsaturated fatty acids (Thomsen et al, 1995a(Thomsen et al, , 1995b.…”
Section: Introductionmentioning
confidence: 76%
“…However, a number of other studies, most of which were conducted in outpatients, have failed to show any changes in plasma lipids (Bonanome et al, 1991;Rasmussen et al, 1993;Walker et al, 1995). The differences in HDL cholesterol on the three diets may relate to the small and non signi®cant differences in fasting glucose which were seen after adjustment for diet order as well as the increase in fat on the high-monounsaturated fat diet.…”
Section: Discussionmentioning
confidence: 98%
“…Although our resources did not permit assessing postprandial responses, previous studies have shown that highmono diets do have the ability to attenuate postprandial glucose responses (Campbell et al, 1994;Rasmussen et al, 1993). This may re¯ect the lower carbohydrate content of these diets and the ability of fat to retard the gastric emptying rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of a high-carbohydrate, low-fat diet in treatment of type 2 diabetes has been questioned, due to carbohydrate-induced increase of triacylglycerol concentrations (American Diabetes Association, 1987;Medical Advisory Committee, 1982;Pedersen O, 1994;Coulston et al, 1987Coulston et al, , 1988. Studies on carbohydrate and lipid metabolism in patients with type 2 diabetes indicate that diets rich in monounsaturated fatty acids (MUFA) may safely be applied (Bonamone et al, 1991;Garg et al, l988, 1992a,b;Campell et al, 1994;Rasmussen et al, 1993). In addition, the MUFA-enriched diet may have bene®cial effect on blood pressure (Rasmussen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%